iPhone App: Lecturer's Room Finder, UUM-CAS - Khunsri, Chulawadee (2011)
The Information Technology building at the College of Arts and Sciences, Universiti Utara Malaysia has a complex design. The numbering of the lecturers’ rooms is very confusing and finding the required room is very difficult and taking a long time not just for students but also for lecturers. The purpose of this study is to develop a mobile indoor navigation prototype for lecturers’ room search based on iPhone. This report discusses about indoor navigation and the development of the prototype based on iPhone. This study utilized the research methodology in Information System (IS) which was adapted from Vaishnavi and Kuechler (2004). The use of mobile indoor navigation prototype could help students to find the required room faster while saving energy and increasing productivity. The mobile indoor navigation prototype was developed using web tools such as PHP, HTML5, CSS, JavaScript and SQLite as database. The prototype can be used as an alternative way in finding lecturers’ room at IT building. The results from the evaluation indicated that mobile indoor navigation application for searching lecturers' room at IT building, College of Arts and Sciences, Universiti Utara Malaysia based on iPhone devices has achieved all the objectives. The users agreed in terms of Perceived Usefulness and Perceived Ease of Use towards the use of the prototype.